2016
DOI: 10.1016/j.stemcr.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Single Primate Neuroepithelial Cell Clonal Expansion System for Neural Tube Development and Disease Studies

Abstract: SummaryDeveloping a model of primate neural tube (NT) development is important to promote many NT disorder studies in model organisms. Here, we report a robust and stable system to allow for clonal expansion of single monkey neuroepithelial stem cells (NESCs) to develop into miniature NT-like structures. Single NESCs can produce functional neurons in vitro, survive, and extensively regenerate neuron axons in monkey brain. NT formation and NESC maintenance depend on high metabolism activity and Wnt signaling. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 50 publications
(68 reference statements)
2
37
0
Order By: Relevance
“…Previous studies showed that inhibitions of TGF/Nodal, Notch and BMP4 signaling pathways or activation of Wnt signaling pathway have the abilities to support the generation of cortical progenitors from PSCs211131415192132333435. To test whether NESCs could be quickly and effectively obtained, hESCs were induced differentiation by the combined usage of inhibitors of TGF/Nodal, Notch and BMP4 pathways supplemented with the agonist of Wnt pathway35 (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that inhibitions of TGF/Nodal, Notch and BMP4 signaling pathways or activation of Wnt signaling pathway have the abilities to support the generation of cortical progenitors from PSCs211131415192132333435. To test whether NESCs could be quickly and effectively obtained, hESCs were induced differentiation by the combined usage of inhibitors of TGF/Nodal, Notch and BMP4 pathways supplemented with the agonist of Wnt pathway35 (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…For neuroectoderm cell differentiation, the differentiation protocol followed our previous reported protocol (Zhu et al, 2016). Briefly, primed monkey PSCs were digested with Collagenase IV (GIBCO) and neural induction was induced by switching from ESC growth media to differentiation media in suspension culture [Advance DMEM/F12 (1:1) (Invitrogen): Neurobasal media (Invitrogen) (1:1 mixture) supplemented with 1xN2 (Invitrogen), 1xB27 (Invitrogen), 10ng/ml bFGF (Millipore), 3 mM CHIR99021 (Cellagen technology), 5 mM SB431542 (Cellagen technology), 0.2 mM Compound E and 0.1 mM LDN193189 (Cellagen technology)].…”
Section: Methods Detailsmentioning
confidence: 99%
“…Although human iPSCs resemble ESCs in terms of morphology, gene expression profile and differentiation potential, some human iPSCs display abnormal epigenetic features and/or genetic mutations (Hussein et al, 2011;Lund et al, 2012;Nazor et al, 2012). To evaluate their chimeric competency, we generated piPSCs from fibroblast cells of fetal and junior cynomolgus monkeys using the Sendai virus or retrovirus cocktails (Zhu et al, 2016), respectively. These piPSCs expressed pluripotent genes, maintained a normal karyotype, and had the potential to differentiate into three germ layers and trophoblast (Figures S1B and S1J).…”
Section: Chimeric Competency Of Primed Pipscs Conferred By a New Embrmentioning
confidence: 99%
“…Research in Xenopus and mouse ESC have shown that homologues of the Hes1 protein are involved in the development of the NC, controlling essential genes required for the differentiation of this cell population (Mendez‐Maldonado, Vega‐Lopez, Caballero‐Chacon, Aybar, & Velasco, ; Vega‐López et al, ). Another mechanism is the increase of cell proliferation and integrin adhesion, and decrease in BMP4 signaling and apoptosis through p53 inhibition (Aujla, Bora, Monahan, Sweedler, & Raetzman, ; Klinck et al, ; Zhu et al, ). Regarding NC development, FA is important for mouse cranial NC morphogenesis, which means that folate deficiency renders NC unable to undergo proper differentiation (Melo, Bressan, Costa‐Silva, & Trentin, ).…”
Section: Nutritional and Maternal Metabolic Factorsmentioning
confidence: 99%